UTILIZATION OF RENEWABLE ENERGY IN MODERN AGRICULTURE IN DENMARK - Nathaniel Ramos; Isabel Martinez; Carloz Fernandez; Ardi Azhar Nampira (Yayasan Adra Karima Hubbi, 2025)
Renewable energy has become an important component in efforts to create sustainable and efficient agriculture in Denmark. The background of this research is the need to improve energy efficiency and agricultural productivity, as well as reduce the environmental impact of fossil energy use. This study aims to evaluate the impact of renewable energy on operational efficiency, agricultural yields, and energy cost reduction. The study used a mixed approach, involving 150 farmers in different regions of Denmark through in-depth surveys and interviews. The results show that renewable energy increases energy efficiency by up to 30%, increases crop yields by 20%, and reduces energy costs by up to 25%. In conclusion, renewable energy not only supports environmental sustainability, but also increases the productivity and profitability of the agricultural sector in Denmark. More research is needed to identify the long-term impacts and more equitable access to renewable energy technologies.